2000
DOI: 10.1152/ajpgi.2000.279.2.g262
|View full text |Cite
|
Sign up to set email alerts
|

Upper esophageal sphincter function during gastroesophageal reflux events revisited

Abstract: Upper esophageal sphincter (UES) function during gastroesophageal reflux events is not completely elucidated because previous studies addressing this issue yielded conflicting results. We reexamined the UES pressure response to intraluminal esophageal pressure and pH changes induced by reflux events. We studied 14 healthy, asymptomatic volunteers (age 49 +/- 6 yr) and 7 gastroesophageal reflux disease patients (age 48 +/- 5 yr). UES pressure, intraesophageal pressure, and pH were monitored at the distal, middl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
39
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 26 publications
2
39
3
Order By: Relevance
“…This finding may be because of increase in muscle mass and therefore stronger contraction or enhanced nerve-muscle interaction. An increase in UES tone has been noted in children and adults during GER events 8,15,27 ; and from our study, an increased level of aerodigestive tract protection is evident with volume increments. Mechanisms such as EUCR may provide airway protection against retrograde aspiration.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This finding may be because of increase in muscle mass and therefore stronger contraction or enhanced nerve-muscle interaction. An increase in UES tone has been noted in children and adults during GER events 8,15,27 ; and from our study, an increased level of aerodigestive tract protection is evident with volume increments. Mechanisms such as EUCR may provide airway protection against retrograde aspiration.…”
Section: Discussionsupporting
confidence: 75%
“…Clearance mechanisms including primary peristalsis (PP), secondary peristalsis (SP) and esophago-upper esophageal sphincter (UES)-contractile reflexes (EUCR) that may prevent the entry of refluxate into the pharynx or larynx are well recognized in healthy adults and those with GER disease. [8][9][10][11] Immaturity, rapid development, and changing feeding behavior distinctly separate evolving pathophysiology in neonates from that of older subjects.Aerodigestive symptoms may result from delayed clearance, airway aspiration, or chemoreceptor stimulation. 12-15 We described methods to evaluate the esophageal body and UES motor responses resulting from esophageal provocation.…”
mentioning
confidence: 99%
“…In fact, we found that experimental acidification enhanced the UES contractile response. This response may protect the esophagus against acid exposure because similar chemostimulatory augmentation of UES pressure has been observed previously during esophageal acid infusion (6) and during spontaneous gastroesophageal acid reflux (25). The upregulation of the UES contractile response by acute esophageal acid infusion observed in healthy controls may not be indicative of UES responses in patients with chronic acid exposure in whom the possibility exists that afferent nerves are desensitized or damaged by prolonged acid exposure.…”
Section: Discussionmentioning
confidence: 51%
“…Although this systematic review did not concentrate on the data pertaining to the prevalence of COPD and GERD, it is important not to ignore the high prevalence of GERD in this population as a concomitant contributor to oropharyngeal swallowing complaints 54,55 , and as an exacerbating factor in respiratory decompensation 14,30,[32][33][34]41,47 .…”
Section: Discussionmentioning
confidence: 99%